Stigma of Women's Freedom in Accessing Higher Education in Kabupaten Deli Serdang - Elvina Tanjung; Friska Chairani; Rholand Muary (International Journal of Cultural and Social Science, 2021)
This study aims to describe the condition of women's education, describe the public's view of women with higher education and describe the public's perception of the importance of higher education for women in Tanjung Morawa, Kabupaten Deli Serdang.This research is a qualitative descriptive study. The subject of this research is the community, the data collection methods in this study are observation, interviews and documentation. Sources of data used in this study are primary data sources and secondary data sources. The results obtained from this study: The educational conditions of women in Tanjung Morawa are dominantly pesantren graduates and women born in the 70-„80s on average only graduated from elementary school. However, now it has experienced developments with the construction of educational facilities and now there are young women in Tanjung Morawa who are starting to continue to higher education, the community views positively women with higher education and hopes that they can apply their knowledge to the community and there are still people who perceive women as It's not important to have a higher education because of their nature in the kitchen, but many people think that higher education is important for women because they will become educators for their children.